Oxidative Stress in Tauopathies: From Cause to Therapy - Fernando Bartolome; Eva Carro; Carolina Alquezar (Antioxidants, 2022)
Oxidative stress (OS) is the result of an imbalance between the production of reactive oxygen species (ROS) and the antioxidant capacity of cells. Due to its high oxygen demand, the human brain is highly susceptible to OS and, thus, it is not a surprise that OS has emerged as an essential component of the pathophysiology of several neurodegenerative diseases, including tauopathies. Tauopathies are a heterogeneous group of age-related neurodegenerative disorders characterized by the deposition of abnormal tau protein in the affected neurons. With the worldwide population aging, the prevalence of tauopathies is increasing, but effective therapies have not yet been developed. Since OS seems to play a key role in tauopathies, it has been proposed that the use of antioxidants might be beneficial for tau-related neurodegenerative diseases. Although antioxidant therapies looked promising in preclinical studies performed in cellular and animal models, the antioxidant clinical trials performed in tauopathy patients have been disappointing. To develop effective antioxidant therapies, the molecular mechanisms underlying OS in tauopathies should be completely understood. Here, we review the link between OS and tauopathies, emphasizing the causes of OS in these diseases and the role of OS in tau pathogenesis. We also summarize the antioxidant therapies proposed as a potential treatment for tauopathies and discuss why they have not been completely translated to clinical trials. This review aims to provide an integrated perspective of the role of OS and antioxidant therapies in tauopathies. In doing so, we hope to enable a more comprehensive understanding of OS in tauopathies that will positively impact future studies.